The Increasing Representativeness of International Organizations' Secretariats: Evidence from the United Nations System, 1997–2015 - Michal Parizek; Matthew D. Stephen (International Studies Quarterly, 2021)
Although international organizations (IOs) and their secretariats play important roles in international politics, we know surprisingly little about their staffing composition and the factors that shape it. What accounts for the national composition of the secretariats of IOs? We theorize that the national composition of international secretariats is shaped by three factors: the desire by powerful states for institutional control, a commonly shared interest in a secretariat's functional effectiveness, and, increasingly, a need for secretariats to be seen as legitimate by being representative of the global population. Building on recent constructivist literature, we argue that IOs face increasing normative pressure to be representative in their staffing patterns. Using panel regression, we assess our argument with a new dataset covering states' representation in the secretariats of thirty-five United Nations system bodies from 1997 to 2015. The results indicate that while functional effectiveness plays a significant and stable role, international secretariats have become increasingly representative of the global population. Moreover, this has come primarily at the expense of the over-representation of powerful states. This shift from power to representation is particularly strong in large IOs with high political and societal visibility. When it comes to IO secretariats, representativeness (increasingly) matters. – – Si bien las organizaciones internacionales (OI) y sus secretarías desempe\~nan un papel importante en la política internacional, sabemos increíblemente poco acerca de cómo se compone su personal y los factores que lo configuran. Cómo se explica la composición nacional de las secretarías de las OI? Planteamos que la composición nacional de las secretarías internacionales está determinada por tres factores: el deseo de control de los estados poderosos; un interés común en la eficacia funcional de una secretaría; y, cada vez más, la necesidad de que las secretarías se consideren legítimas por ser representativas de la población mundial. Basándonos en la literatura constructivista reciente, sostenemos que las OI enfrentan una presión normativa cada vez mayor para ser representativas en sus patrones de contratación de personal. Utilizando el modelo de regresión de panel, evaluamos nuestro argumento con un nuevo conjunto de datos que abarca la representación de los estados en las secretarías de 35 órganos del sistema de las Naciones Unidas entre 1997 y 2015. Los resultados indican que, si bien la eficacia funcional juega un papel importante y estable, las secretarías internacionales se han vuelto cada vez más representativas de la población mundial. Además, esto se ha producido principalmente a expensas de la sobrerrepresentación de los estados poderosos. Este cambio del poder a la representación es particularmente fuerte en las OI grandes con alta visibilidad política y social. Cuando se trata de secretarías de OI, la representatividad importa (cada vez más).
Keywords: 300